Distributed Search by Constrained Agents Algorithms, Performance, Communication - Meisels, Amnon (Advanced Information and Knowledge Processing, 2008)
Agent technology is evolving as a leading field of research connected to diverse areas such as A.I., E-commerce, robotics and information retrieval. Agents systems use reasoning and constraint-based reasoning that has a wide potential for representing multiple types of problems. A fundamental building block within all these areas is the ability to perform search and an inherent part of all agents must therefore relate to distributed and cooperative methods of search. This book presents a comprehensive discussion on the field of distributed constraints, its algorithms and its active research areas. It introduces distributed constraint satisfaction and optimization problems and proceeds to present a complete state-of-the-art in DisCSP & DisCOP research. The presentation assumes no prior knowledge of constraints or distributed constraints. Features and topics: • Introduces in great detail search algorithms for DisCSPs and DisCOPs • Presents a comprehensive study of distributed performance measures for all algorithms, allowing an extensive experimental evaluation to be constructed • Addresses potential problems following current research on DisCSPs and DisCOPs • Discusses the impact of communication quality on distributed search (for example message delays) • Describes the most significant recent research in the field of distributed constraints satisfaction and optimization, including its difficulties This exposition of the many elements of distributed search algorithms for DisCSPs and DisCOPs will be a research asset and an invaluable read for researchers and graduate students who focus on distributed CSPs and COPs. In addition, the book's comprehensiveness and style make it an ideal tool for a graduate course on distributed search in AI. Professor Amnon Meisels has an active research group who have worked in distributed constraints for a number of years and has published extensively in the field. He is a member of the Department of Computer Science at Ben-Gurion University, Beer-Sheva, Israel.